Licensed Bacille Calmette-Guérin (BCG) formulations differ markedly in bacterial viability, RNA content and innate immune activation. Issue 9 (24th February 2020) - Angelidou, Asimenia; Conti, Maria-Giulia; Diray-Arce, Joann; Benn, Christine S.; Shann, Frank; Netea, Mihai G.; Liu, Mark; Potluri, Lakshmi Prasad; Sanchez-Schmitz, Guzman; Husson, Robert; Ozonoff, Al; Kampmann, Beate; et al.
Highlights: BCG, given to millions of infants, induces both specific and heterologous effects. BCG viability is important for vaccine-induced immunogenicity & protection in vivo . We compared licensed BCGs produced by different manufacturers head-to-head. We found marked variability in the content of live mycobacteria across BCGs. BCG viability correlates with immunostimulatory capacity in human blood in vitro . Identification of optimal BCG formulations for early life immunization is needed. Graphical abstract: Abstract: Background: Bacille Calmette-Guérin (BCG), the live attenuated tuberculosis vaccine, is manufactured under different conditions across the globe generating formulations that may differ in clinical efficacy. Innate immune recognition of live BCG contributes to immunogenicity suggesting that differences in BCG viability may contribute to divergent activity of licensed formulations. Methods: We compared BCG-Denmark (DEN), -Japan (JPN), -India (IND), -Bulgaria (BUL) and -USA in vitro with respect to a) viability as measured by colony-forming units (CFU), mycobacterial membrane integrity, and RNA content, and b) cytokine/chemokine production in newborn cord and adult peripheral blood. Results: Upon culture, relative growth was BCG-USA > JPN ≫ DEN > BUL = IND. BCG-IND and -BUL demonstrated >1000-fold lower growth than BCG-JPN in 7H9 medium and >10-fold lower growth in commercial Middlebrook 7H11 medium. BCG-IND demonstrated significantly decreased membrane integrity, lower RNA content, and weaker IFN-γ inducing activity in whole blood compared to other BCGs. BCG-induced whole blood cytokines differed significantly by age, vaccine formulation and concentration. BCG-induced cytokine production correlated with CFU, suggesting that mycobacterial viability may contribute to BCG-induced immune responses. Conclusions: Licensed BCG vaccines differ markedly in their content of viable mycobacteria possibly contributing to formulation-dependent activation of innate and adaptive immunity and distinct protective effects.